Studi Pengawasan dan Pengusahaan Sarang Burung Walet Dalam Meningkatkan Pendapatan Asli Daerah Kabupaten Kutai Barat: Study of Supervision and Swallow's Nest Entrepreneurship in Increasing District Revenues of Kutai Barat - E. Letizia Dyastari; Erwin Resmawan; Rita Kala Linggi; Wilson Pasaribu (JOURNAL OF GOVERNMENT SCIENCE, 2021)
This research describes and analyze supervision of Kutai Barat District Government toward swallow’s nest entrepreneurship with a purpose to increase district revenues. The type of the research is descriptive qualitative analysis, based on data collected through interviews, observation, and documentary study. It has been found that government’s supervision team has cooperated with Quarantine Service to deal with this kind of business, and tax payment through e-payment has been imposed and realized. Tax revenues are however not promising as supervision are not optimum, indicated by the fact that many swallow’s nest artificial houses are not built with legal permission, no sanctions have been imposed to the rule breakers, and many text payers of swallow’s nests businesses do not realize their tax obligation.